2001
DOI: 10.1074/jbc.m102067200
|View full text |Cite
|
Sign up to set email alerts
|

E2F Transcriptional Activation Requires TRRAP and GCN5 Cofactors

Abstract: The E2F family of transcription factors regulates the temporal transcription of genes involved in cell cycle progression and DNA synthesis. E2F transactivation is antagonized by retinoblastoma protein (pRb), which recruits chromatin-remodeling proteins such as histone deacetylases and SWI⅐SNF complexes to the promoter to repress transcription. We hypothesized that E2F proteins must reverse the pRb-imposed chromatin structure to stimulate transcription. If this is true, E2F proteins should recruit proteins capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 70 publications
5
101
0
1
Order By: Relevance
“…Because E2F-1 has been shown to interact with TRRAP, a subunit of several histone acetyltransferase complexes, E2F-1 may be responsible for the recruitment of Tip60 to the MYCN promoter (35,36). In contrast, binding of E2F and Sp1/Sp3 did not correlate with the nucleosome remodeling that accompanies the switch from basal to full promoter activity.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Because E2F-1 has been shown to interact with TRRAP, a subunit of several histone acetyltransferase complexes, E2F-1 may be responsible for the recruitment of Tip60 to the MYCN promoter (35,36). In contrast, binding of E2F and Sp1/Sp3 did not correlate with the nucleosome remodeling that accompanies the switch from basal to full promoter activity.…”
Section: Discussionmentioning
confidence: 67%
“…E2F-1 has been shown to interact with the histone acetyltransferase p300/CBP and with TRRAP, a component of several histone acetyltransferase complexes that contain either Gcn5 or Tip60 as the enzymatically active subunit (35)(36)(37). However, recruitment of co-factors, histone acetylation, and loading of RNA polymerase can occur prior to the binding of a nuclear extract from the neuroblastoma cells lines SH-EP, SY5Y, and IMR-32.…”
Section: Sp1 and Sp3 Activate The Mycn Promoter And Synergize With E2mentioning
confidence: 99%
“…These include c-Myc, p53, E2F1, E2F4, E1A, ERa, ERb, VDR, PPARg, LXR, FXR, b-catenin, Skp1 and BRCA1 Lang et al, 2001;Park et al, 2001;Ard et al, 2002;Yanagisawa et al, 2002;Lang and Hearing, 2003;Unno et al, 2005;Cheng et al, 2006;Oishi et al, 2006;Sierra et al, 2006;Finkbeiner and Herceg, unpublished results). Interestingly, the TRRAP domains that interact with diverse partners are not overlapping and it can be speculated that TRRAP may serve not only as a scaffold for HAT complexes but also as a platform for recruitment of different regulatory factors and complexes to chromatin.…”
Section: Cellular Pools Of Trrapmentioning
confidence: 91%
“…The TRRAP (TRansformation/tRanscription domainAssociated Protein) and its yeast homolog Tra1, remarkably large proteins with homology to the phosphatidyl-inositol-3-kinase (PI3K) family members are common components of many HAT complexes in yeast and mammalian cells (Grant et al, 1998;Vassilev et al, 1998;Allard et al, 1999;Brand et al, 1999;Ikura et al, 2000;Pray-Grant et al, 2002;Sterner et al, 2002). TRRAP was originally identified in the Michael Cole's laboratory as an interacting partner of c-Myc , and subsequent studies showed that several other transcription factors including E2F and nuclear receptors interact with TRRAP Lang et al, 2001;Yanagisawa et al, 2002;Fan et al, 2004). Interestingly, TRRAP/Tra1 appears to be the only component through which HAT complexes (either histone H3 acetylating complexes or those with preference for histone H4) contact transcription activators (Brown et al, 2001;Bhaumik et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation